Improving Medication Adherence and Lifestyle Changes: An Image-Based Educational Tool for Patients with Heart Failure - Gao L; Xie Q; Liu T; Liu H; Yan S; Han Y; Zhang M; Zhu D; Guo N; Nicholas S; Maitland E; Wang D (Patient Preference and Adherence, 2025)
Lingyan Gao,1 Qing Xie,1 Tiantian Liu,1 Hua Liu,1 Suying Yan,1 Yalei Han,2 Meijing Zhang,2 Dawei Zhu,3 Na Guo,4 Stephen Nicholas,5,6 Elizabeth Maitland,7 Dongxiao Wang1 1Department of Pharmacy, Aerospace Center Hospital, Beijing, People’s Republic of China; 2Department of Cardiology, Aerospace Center Hospital, Beijing, People’s Republic of China; 3International Research Center for Medicinal Administration, Peking University, Beijing, People’s Republic of China; 4Department of Strategic Research, China Population and Development Research Center, Beijing, People’s Republic of China; 5Health Services Research and Workforce Innovation Centre, Newcastle Business School, University of Newcastle, Newcastle, NSW, Australia; 6Australian National Institute of Management and Commerce, 1 Central Avenue Australian Technology Park, Sydney, Australia; 7School of Management, University of Liverpool, Liverpool, UKCorrespondence: Dongxiao Wang, Department of Pharmacy, Aerospace Center Hospital, No. 15 Yuquan Road, Haidian District, Beijing, 100049, People’s Republic of China, Tel +86 13520109984, Email baixiao301@163.comBackground: A lack of disease-specific knowledge in heart failure (HF) patients is associated with poor adherence to complex medication regimens and non-pharmacological recommendations, especially among individuals with low health literacy. Existing educational tools have been shown to be inadequate, highlighting the need for more accessible and effective alternatives.Purpose: To develop an educational tool that improves HF knowledge in a more accessible and effective way.Methods: An image-based educational tool was created by healthcare professionals and HF patients, drawing on the Health Belief Model (HBM) and utilizing both qualitative and quantitative approaches. Project objectives were defined and content was guided by a literature review and focus group interviews. The tool was refined through iterative optimization using feedback and questionnaires.Results: Thirteen healthcare professionals and eight HF patients participated in the development and refinement of the educational tool. The final tool consisted of seven A3-sized images and accompanying text, addressing the following topics: (1) Cognition of HF; (2) Cause and classification of HF; (3) Inducing factors and prevention of HF; (4)-(5) Medication treatments of HF; (6) Exercise and self-management of HF; (7) “We are on the same journey” - a supportive theme for HF patients. The final version of the tool demonstrated high accuracy, readability, usability, and overall satisfaction, with all categories receiving scores of ≥ 4.5 on a 5-point Likert scale.Conclusion: The image-based educational tool, developed using HBM, effectively meets the needs of HF patients. It shows strong performance in terms of accuracy, readability, usability, and satisfaction, which may ultimately help improve adherence to both pharmacological treatments and non-pharmacological recommendations for HF management.Keywords: patient education, image-based educational tool, patient engagement, heart failure, medication adherence, lifestyle changes